Variations in epidermal trichomes of a mystic weed Parthenium hysterophorus L. from semi-arid regions of Barmer, Rajasthan (India) - Vimala,; Hans, Dinesh (Frontiers in Plant Science, 2024)
The Asteraceae family of plants, which has 16,000-17,000 genera and 24,000-30000 species, is diverse and widely spread, notably in the tropics and subtropics. Asteraceae has capitula head bracket traits that are unique to this genus of plants. This study's goal was to identify the micro-morphological makeup of the trichomes in Parthenium hysterophorus L. Invasive weed Parthenium hysterophorus L. is erect, short-lived fast-growing plant is found in hot areas and is known for its luxuriant growth. As the stem attains maturity, becomes harder. Mature stems are greenish and coated in tiny, soft hairs called hirustles. Later leaves are simple and deeply pinnatifid, while early leaves create a rosette habitat. Hundreds of tiny flower heads, or capitulum, are arranged in clusters at the apex of the branches. Trichomes are epidermal appendages that are frequently seen on the leaves, stems, and fruits of plants. There are two types of trichomes: glandular and non-glandular. The immature leaves and stem of Parthenium hysterophorus L. were cut into slices, the layers were removed, and the specimen was examined at X4, X10, X40, and X100 magnifications under light microscope. The sample was taken from the stem, which was located one to three centimeters from the tip. 14 different types of trichomes, including cylindrical, moniliform, simple uniseriate, non-glandular sessile, and palate types of glandular trichomes, are observed on the leaves, petiole, and stem of Parthenium hysterophorus L. These trichomes are primarily identified based on their structural differences. Trichomes are an important taxonomic tool for differentiating between species and genera. In respect to aridity, the study presents several new features that give future taxonomists a basic understanding of trichome diversity.